Masuk Angin dalam Konteks Kosmologi Jawa - Atik Triratnawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This study examines the meaning of masuk angin among the Javanese society, by the ethnographic approach. In this context, the meaning of masuk angin cannot be separated fromJavanese cosmological doctrine, especially in relation to health and human body. In Javanese cosmology, being healthy or ill is perceived as the result of condition of equilibrium. Thus, the therapy for illness or masuk angin should be conducted by restoring the equilibrium.